2020
DOI: 10.1039/c9dt04620h
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic reaction mechanisms. A personal journey

Abstract: This review describes a personal journey over the past two decades highlighting experimental and computational mechanistic studies in inorganic chemistry performed with numerous PhD students, post-docs, visiting scientists and colleagues from abroad.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 309 publications
0
14
0
Order By: Relevance
“…The kinetics of the reaction between CblOH 2 + and PA with the PA concentration in excess compared to the concentration of CblOH 2 + was also studied at lower pH conditions. A preliminary report on this work was recently included in an extended Perspective article for Dalton Transactions . In this work, a buffered anaerobic solution of CblOH 2 + (0.10 M Tris buffer pH 7.2, 25 °C, Ar atmosphere) was added to an aqueous anaerobic solution of PA. Changes in the UV–vis spectrum were recorded using a stopped-flow instrument.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The kinetics of the reaction between CblOH 2 + and PA with the PA concentration in excess compared to the concentration of CblOH 2 + was also studied at lower pH conditions. A preliminary report on this work was recently included in an extended Perspective article for Dalton Transactions . In this work, a buffered anaerobic solution of CblOH 2 + (0.10 M Tris buffer pH 7.2, 25 °C, Ar atmosphere) was added to an aqueous anaerobic solution of PA. Changes in the UV–vis spectrum were recorded using a stopped-flow instrument.…”
Section: Resultsmentioning
confidence: 99%
“…A preliminary report on this work was recently included in an extended Perspective article for Dalton Transactions. 53 In this work, a buffered anaerobic solution of CblOH 2 + (0.10 M Tris buffer pH 7.2, 25 °C, Ar atmosphere) was added to an aqueous anaerobic solution of PA. Changes in the UV−vis spectrum were recorded using a stopped-flow instrument. Figures 9a and S11a show typical UV−vis spectral changes for the reaction of CblOH 2 + (λ max = 275, 351, 412, 497, 525 nm) with excess PA. Once again CblNO is formed (λ max = 321, 480 nm 26,38 ), and three isosbestic points were observed at 340, 367, and 498 nm.…”
Section: Kinetic Studies On the Reaction Of Cblohmentioning
confidence: 99%
“…These complexes are by one or two orders of magnitude less labile than the en analogue, for the aquation and water substitution reactions by chloride and thiourea at 25 °C, respectively. 28 …”
Section: Introductionmentioning
confidence: 99%
“…We concluded that the rate of displacing a monodentate ligand, the rst step of the proposed mechanism of the catalytic NAD + -NADH conversion, depends on the electronic and steric effects provided by bidentate ligands. [25][26][27][28] Based on these studies, we expect that the catalytic efficiency will depend markedly on the nature of the coordinated bidentate ligand. The same effect was also observed for organometallic complexes studied by Sadler et al 17,18,21 Therefore, we extended our work to the [Ru II (terpy)(ampy)Cl]Cl (ampy ¼ 2-(aminomethyl)pyridine) and [Ru II (terpy)(bipy)Cl]Cl$2H 2 O (bipy ¼ 2,2 0 -bipyridine) complexes.…”
Section: Introductionmentioning
confidence: 99%
“…16 Density functional theory (DFT) calculations have been employed to interpret experimental results and to understand the coordination character of PGM complexes. 17,18 Recently, the DFT applications to the Rh and Pd complexes with H 2 O and NO 3 À ligands, considering the geometrical isomers for the unidentate system, have been reported by combining them with experimental techniques. 19,20 Watanabe et al studied the coordination bond lengths and electronic transitions of [Pd(NO 3 )-…”
Section: Introductionmentioning
confidence: 99%